Development of Social Emotional Learning - Rozi Sastra Purna; Nurmina (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Social interactions that occur through the media make students' social interactions in the real world weakened. Students become less competent on social-emotionally, even this problem affects their academic performance. Moreover, social and emotional competence is quite important for students. Research shows that mastering of social-emotional competency is related to the better improvement of the school welfare and its performance. While failure to achieve competence in this field can lead to various personal, social, and academic difficulties. The aim of this article is viewing about Social Emotional Learning (SEL). Social Emotional Learning (SEL) is an approach that can be used by the teachers to improve the success of students in the school and their life.The usage of technology can be an alternative on approaching of social emotional Learning (SEL). The technology provides many conveniences, as well as a new way of transferring knowledge in the schools.Each innovation is created to provide positive benefits for human life, including in the teaching and learning process in the schools.Actually, many countries in the world have started developing SEL in their schools. However, there are still few countries who use technology media as the part of the SEL program.The technology that is developing at this time can be used as a learning medium to develop social emotional learning in the schools. Schools as the place for teaching and learning process must be able to utilize media technology as a teaching aid. Activities those are supported by a set of digital tools can guide them through a series of structured tasks which are designed to encourage the students' understanding of culture, the guide interaction, the problem solving and decision making about the social and emotional issues.The learning tools for SEL development can be in the form of digital stories and animations, as well as the discussions with the online instruction guides.